VD_FINDINFO HC / 2025 / 27 vom 6. Januar 2025 - VD Tribunal cantonal (2025)
PROCÈS DEVENU SANS OBJET, DÉPENS, DROIT D'OBTENIR UNE DÉCISION, RETARD INJUSTIFIÉ | 106 al. 1 CPC (CH), 242 CPC (CH), 319 let. c CPC (CH)